Experiences of Prison Detention Whilst Seeking Asylum in Aotearoa New Zealand: An Exploratory Study - Hiew, Eunice (Auckland University of Technology, 2021)
The world is currently witnessing the highest levels of forcibly displaced people on record, as escalating regional wars and human rights violations force people to seek sanctuary in other lands. Asylum seekers have been described as one of the most “at risk” populations in the world. Yet, Eurocentric nations have been using various measures to deter people from seeking asylum in their countries. The most controversial of these involves the placement of asylum seekers in detention centres. Given that asylum seekers have frequently been subject to (often multiple) traumatic experiences, it is concerning that they are being placed into contexts where there is the risk of further harm; detention has been robustly demonstrated in the international literature to have a negative association with asylum seeker health; particularly mental health. However, there is a paucity of research on individuals’ experiences of detention in Aotearoa. This study aimed to add knowledge to that gap, by exploring the experiences of individuals formerly detained whilst seeking asylum in Aotearoa. Furthermore, in Aotearoa, there is the potential for detention in prison; over the last five years, 80 individuals seeking asylum in Aotearoa have been detained in prison for long periods of time; an average of 166 days. To this author’s knowledge, details on specifically prison (and, by extension, with persons incarcerated for crime-related reasons [PICRs]) versus other types of detainment are minimal. The little knowledge that exists of detained asylum seekers in Aotearoa suggests potential risk of harm that gives further cause for concern. This study aimed to further the knowledge around prison detention. Interviews were conducted with six individuals who had been formerly detained whilst seeking asylum in Aotearoa. Reflexive thematic analysis was used to analyse transcripts. An overarching theme was identified: detention caused suffering. Furthermore, this study identified particular aspects of the detention experience – during detention and after release - that were related to psychological and/or physical distress. Three themes were conceptualised to understand these aspects: powerlessness (theme one), the interaction of detention experiences with the asylum seeker identity and story (theme two), and distress related to processes (theme three). Distress related to theme one was conceptualised through four sub-themes: experiences being locked up with PICRs; lack of access to the ability to support oneself (notably through a lack of work visa) after release; how the care, responsivity and competence of people in power had meaningful consequences on asylum seekers’ lives; and experiences of coping and resilience amidst circumstances with restricted access to power. Distress related to theme two was conceptualised through two sub-themes: unfairness of treating asylum seekers like PICRs, and the compounding effect of detention on pre-migration suffering making matters worse. Distress related to theme three was conceptualised through two sub-themes: the inability to contact family, and lack of knowing. There was variation in the overall levels of suffering during, and after, detention, suggesting that there were a variety of factors that might – negatively or positively - influence asylum seekers’ health. Importantly, despite variation in experiences, suffering appeared to be a defining characteristic of portions, and/or the overall, experience of detention for participants. The findings suggest that there is a higher likelihood of experiences that cause suffering to be present in prison, with a consequent greater risk of harm, for asylum seekers during, and after, detention.
Keywords: Prison detention; Detention; Asylum seekers; Detained